Catastrophe of the Great Economic Depression of 1929: The Case of India - Kaur, Manleen (IISER Mohali, 2020)
The Great Economic Depression of 1929 marked the failure of free market mechanism. Smithian argument of ‘supply creates its own demand’ failed to correct the disequilibrium in the market which left the industries with a huge inventory. The prices spiralled in downward direction which resulted to increased costs and shut down of firms. Consequently, the world got a blow of mass unemployment. At that time J.M. Keynes suggested that the role of the government is crucial for correcting the disequilibrium. He endorsed a demand-side approach and recommended expansionary fiscal policy, that is, low taxation and high expenditure on public infrastructure. However, despite Keynes’ strong proposition for a fiscal expansion to correct deflation, the British Empire continued with its orthodox approach to maintain surplus in balance of payments account. In case of India, the phase of depression was marked by contractionary monetary and fiscal policies. The colonial government in India maintained a high bank rate which hindered the growth of industrial sector. Simultaneously, it reduced public expenditure in irrigation which severely affected the agriculturists who were already burdened under high land revenue rates. The government’s hesitation to reduce the financial burden on cultivators and landless labours led to the problem of distress gold. Therefore, the economic depression proved to be an opportunity for the British to extract a high amount of gold and other resources from India while it was a blow to the Indian population who parted with their savings merely for their subsistence. Thus the research critically analyses the government policies adopted during the Great Economic Depression of 1929 using the government documents and scholarly works. The doctoral work also takes into account the public discourse during the period under consideration by referring to various Indian and British newspapers. It also highlights the process of change from Classical to Keynesian school of economic thought in economies worldwide, with special reference to India.
Keywords: Economic Depression of 1929; Economic History; Indian Economy; Emergence of Monetarism